Reactions of nitroxide radicals in aqueous solutions exposed to non-thermal plasma: limitations of spin trapping of the plasma induced species. (31st August 2016) - Gorbanev, Yury; Stehling, Nicola; O'Connell, Deborah; Chechik, Victor
Abstract: Low temperature ('cold') atmospheric pressure plasmas have gained much attention in recent years due to their biomedical effects achieved through the interactions of plasma-induced species with the biological substrate. Monitoring of the radical species in an aqueous biological milieu is usually performed via electron paramagnetic resonance (EPR) spectroscopy using various nitrone spin traps, which form persistent radical adducts with the short-lived radicals. However, the stability of these nitroxide radical adducts in the plasma-specific environment is not well known. In this work, chemical transformations of nitroxide radicals in aqueous solutions using a model nitroxide 4-oxo-TEMPO were studied using EPR and LC-MS. The kinetics of the nitroxide decay when the solution was exposed to plasma were assessed, and the reactive pathways proposed. The use of different scavengers enabled identification of the types of reactive species which cause the decay, indicating the predominant nitroxide group reduction in oxygen-free plasmas. The 2 H adduct of the PBN spin trap (PBN-D) was shown to decay similarly to the model molecule 4-oxo-TEMPO. The decay of the spin adducts in plasma-treated solutions must be considered to avoid rendering the spin trapping results unreliable. In particular, the selectivity of the decay indicated the limitations of the PTIO/PTI nitroxide system in the detection of nitric oxide.